2011
DOI: 10.1523/jneurosci.1589-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Age-Related Cognitive Decline and Neurodegeneration, Caused by Deficient DNA Repair

Abstract: Age-related cognitive decline and neurodegenerative diseases are a growing challenge for our societies with their aging populations. Accumulation of DNA damage has been proposed to contribute to these impairments, but direct proof that DNA damage results in impaired neuronal plasticity and memory is lacking. Here we take advantage of Ercc1 ⌬/Ϫ mutant mice, which are impaired in DNA nucleotide excision repair, interstrand crosslink repair, and double-strand break repair. We show that these mice exhibit an agede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 82 publications
7
96
3
Order By: Relevance
“…The upregulation of these classes of proteins marks an increased recruitment of astrocytes and/or other glial cells indicating an increase in neuronal damage and inflammation in the cerebellum of KO mice. This is in line with previous studies that have shown that aging and the lack of efficient DNA repair can trigger neurodegenerative and inflammatory processes (23,(25)(26)(27). Other proteins found to be up-regulated are extracellular proteins that are known to interact with or modify the extracellular environment (HTRA1 and Lama2) as well as cell adhesion molecules (PECAM-1 and MCAM).…”
Section: Resultssupporting
confidence: 91%
“…The upregulation of these classes of proteins marks an increased recruitment of astrocytes and/or other glial cells indicating an increase in neuronal damage and inflammation in the cerebellum of KO mice. This is in line with previous studies that have shown that aging and the lack of efficient DNA repair can trigger neurodegenerative and inflammatory processes (23,(25)(26)(27). Other proteins found to be up-regulated are extracellular proteins that are known to interact with or modify the extracellular environment (HTRA1 and Lama2) as well as cell adhesion molecules (PECAM-1 and MCAM).…”
Section: Resultssupporting
confidence: 91%
“…Similarly, following Cre expression in Purkinje cells, Xpa c/À /Csb m/m mice showed asynchronous loss of Purkinje neurons. Such an asynchronous neuronal degeneration is consistent with cell death resulting from the accumulation of stochastic DNA damage, and strongly resembles the pattern of neuronal degeneration in forebrain and cerebellum specific ERCC1-deficient mice (Borgesius et al, 2011;de Graaf et al, 2013).…”
Section: Neuron-specific Inactivation Of Xpa Triggers Progressive Neusupporting
confidence: 67%
“…Mechanistic overlap is also suggested by overlapping gene expression profiles (Schumacher et al, 2008). Furthermore, neurodegenerative features of our neuron-specific Xpa-deficient Csb m/m mice strongly resemble the neurodegenerative features of mice with neuron-specific deletion of Ercc1 (Borgesius et al, 2011). A potential lesson from Ercc1-deficient mice for the interpretation of the short life span exhibited by Csb m/m /Xpa À/À and Xpg À/À mutant mice, is that restoring Ercc1 expression specifically in the liver via intercrossing with a liver-specific Ercc1 transgenic mouse line, results in considerable reduction of weight loss and a prolonged life span (Selfridge et al, 2001).…”
Section: Severe Short-living Phenotypes In Xpf/ercc1-deficient Micesupporting
confidence: 55%
See 1 more Smart Citation
“…Global Ercc1 mutants as well as neuron-specific Ercc1 mutants exhibit an age-dependent decrease in neuronal plasticity, and progressive neuronal pathology, suggestive of neurodegenerative processes [24]. These mice do not show frank AD pathology (Keene et.…”
mentioning
confidence: 99%